Rancang Bangun Monitoring Daya Listrik untuk Aplikasi Sistem Tenaga Surya Berteknologi Smart Grid pada Skala Rumah Tinggal - Mukhamad Angga Gumilang; Hariyono Rakhmad (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2020)
Utilization of solar cells can be used as a source of residential energy as a backup power source other than relying on supplies from PLN. In previous studies have not developed a system that monitors the power obtained from the utilization of solar cells. As a power monitoring tool a microcontroller and Internet-based (IOT) device is needed to provide information on the availability of backup power in the installation of solar power plants in homes. In this research, a PLTS design that is equipped with an IOT-based power monitoring system uses Arduino Uno and Thinkspeak. The results of the design can be applied to real conditions for the installation of solar power plants for residential homes.